2020
DOI: 10.1002/jlb.2mr1119-224r
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of soluble CD137 in the regulation of immune responses and for immunotherapeutic intervention

Abstract: CD137 is a potent costimulatory receptor. Several agonistic anti‐CD137 antibodies are currently in clinical trials for tumor immunotherapy. Soluble forms of CD137 (sCD137) are generated by differential splicing and antagonize the activities of membrane‐bound CD137 (mCD137) and of therapeutic CD137 agonists. sCD137 is found in sera of patients suffering from autoimmune diseases where it is a natural regulator of immune responses, and which has therapeutic potential for immune‐mediated diseases. This review summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 74 publications
1
43
0
Order By: Relevance
“…Interestingly, the costimulatory molecule CD137 is also low in R patients. This protein, which acts as a T cell activator and membrane-bound molecule, in soluble form, prevents the activation of T cells and the maturation of antigen-presenting cells such as dendritic cells [25].…”
Section: Sics Are Differently Modulated According To Ecog Ps Scalementioning
confidence: 99%
“…Interestingly, the costimulatory molecule CD137 is also low in R patients. This protein, which acts as a T cell activator and membrane-bound molecule, in soluble form, prevents the activation of T cells and the maturation of antigen-presenting cells such as dendritic cells [25].…”
Section: Sics Are Differently Modulated According To Ecog Ps Scalementioning
confidence: 99%
“…Results from a mouse model of CD showed that treatment with anti-4-1BB monoclonal antibodies seemed to have an anti-inflammatory effect in the colon and increased proportions of splenic CD8 + T cells (32). Interestingly, we observed decreased levels of 4-1BB in serum in patients with active LC compared to controls and it is possible that the soluble form of 4-1BB can act as a decoy molecule and then instead have an inhibitory effect (33). APRIL (a proliferation-inducing ligand) and BAFF (B cell activating factor), expressed on myeloid cells, are involved in the differentiation and survival of B cells (34).…”
Section: Discussionmentioning
confidence: 60%
“…In particular, the levels of sCD137 and sCD28 during anti-PD-1 treatment resulted signi cantly enhanced. CD137 and CD28 are known as costimulatory receptors but previous studies have shown that their soluble forms have an inhibitory role in immune response [30,31].…”
Section: Discussionmentioning
confidence: 99%